2015
DOI: 10.7750/biodiscovery.2015.15.1
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 inhibition causes repression of ATM and ATR expression leading to aberrant DNA Damage Response

Abstract: Nuclear factor (erythroid-derived 2)-like 2 (NRF2) is a master regulator of the antioxidant response (AR) pathway and functions as a transcription factor for basal and oxidative stress-induced expression of a battery of detoxification enzymes and cytoprotective genes. Recent evidence has also demonstrated a role of NRF2 in driving resistance of numerous cancers to chemotherapeutic agents. ATM and ATR are serine/threonine kinases that are activated following DNA damage and function as central components of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Hence, we checked the response of NRF2 upon UV‐B treatment by western blot and confocal imaging (Figure a,b) and observed that NRF2 is a UV‐B responsive gene that localizes from the nucleus to the cytoplasm. Further, another study showed NRF2 is required for ATR expression, which coincides with our study (Khalil & Deeni, ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, we checked the response of NRF2 upon UV‐B treatment by western blot and confocal imaging (Figure a,b) and observed that NRF2 is a UV‐B responsive gene that localizes from the nucleus to the cytoplasm. Further, another study showed NRF2 is required for ATR expression, which coincides with our study (Khalil & Deeni, ).…”
Section: Resultssupporting
confidence: 93%
“…Hence, we checked the response of NRF2 upon UV-B treatment by western blot and confocal imaging (Figure 3a,b) and observed that NRF2 is a UV-B responsive gene that localizes from the nucleus to the cytoplasm. Further, another study showed NRF2 is required for ATR expression, which coincides with our study (Khalil & Deeni, 2015). -------------------------------- The decisive fate of the cells exposed to UV is the sum of all the events that may lead to repair, recovery, mutation and cancer or cell death by apoptosis.…”
Section: Uv-b Activates Pak1 Via Cpds At Nuclear Level By a Leptomycin Sensitive Signalsupporting
confidence: 90%
“…In turn, this suggests that Heme oxygenase inhibitors could represent a potential therapeutic strategy. Following the findings of the role of NRF2 in chemoresistance, researchers have focussed on identifying NRF2 inhibitors to modulate NRF2 to overcome chemoresistance [51,55,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] .…”
Section: Nrf2 Signalling Pathway and Regulationmentioning
confidence: 99%
“…Regulation of these genes by NRF2 is therefore likely to influence resistance. Expression of both Ataxia telangiectasia mutated (ATM) and Ataxia telangiectasia and Rad3 related (ATR) are under NRF2 control [ 212 ] . The repression of total ATM and ATR protein levels following NRF2 inhibition suggests transcriptional regulation of these kinases by NRF2.…”
Section: Nrf2 and Its Interaction With Dna Damage Pathwaysmentioning
confidence: 99%
“…However, very few reports exist for transcriptional regulation of ATM and ATR. Inhibition of Nuclear factor like-2 (NRF2), a transcription factor, has been reported to cause transcriptional repression of ATM and ATR[55]. Peng et al have reported that downregulation of DNA-PKcs causes transcriptional repression of ATM[56].…”
mentioning
confidence: 99%